Design, Fabrication, and Screening of Environmental‐Thermal Barrier Coatings Prepared by Ultrafast High‐Temperature Sintering - Xie, Hua; Champagne, Victor K.; Zhong, Wei; Clifford, Bryson; Liu, Shufeng; Hu, Liangbing; Zhao, Ji‐Cheng; Clarke, David R. (Advanced functional materials, 2024)
The demand for more efficient gas turbines relies heavily on the development of new environmental‐thermal barrier coatings (ETBCs). However, there is still uncertainty about which alloys and composites will be used for the next generation of turbine blades, as well as the most promising coating materials. Herein, an ETBCs development strategy is presented by integrating the coating design, synthesis, and screening using an ultrafast high temperature sintering (UHS) technique to accelerate coating improvements. The initial basis for composition selection is their thermal expansion mismatch with the substrate alloys; for which a temperature‐dependent coefficient of thermal expansion database is created. By combining tape casting method with the UHS technique a high‐throughput synthesis of single and multi‐layer coatings are realized with different compositions, layer stacking sequences, and layer thicknesses. To evaluate the coatings, thermal cycling tests from room temperature to 1300 °C are conducted. The approach enabled coatings on objects with complex geometries, multi‐layer ETBCs, and porosity tailoring by using staged UHS that runs with different temperatures and durations. The fast iteration strategy is more cost‐effective for the screening of ETBCs compared to conventional methods and greater throughput which can be further extended for rapid optimization of other materials systems. A fast development strategy of environmental‐thermal barrier coatings is presented by integrating the coating design, synthesis, and screening using an ultrafast high‐temperature sintering technique to accelerate improvements in coating performance. This accelerated strategy offers cost savings for ETBC screening, due to reduced capital expenses and great throughput. Meanwhile, this approach holds promise for the rapid optimization of broader material systems.